IMMUNITY AND LENIENCY POLICY IN COMPETITION CASES - Ana-Maria UDRISTE; Adelina VOICU (Challenges of the Knowledge Society, 2017)
It is fully known that the premises for market economics resides on free competition. In other words, market player must make all the necessary efforts in order to obtain the desired results on their own, through business innovation and increased efficiency. In order to protect this, the competition primary and secondary legislation is carefully tailored to such needs, supporting and protecting the internal market from the companies’ tendency to distort competition. As such, competition law offers the companies’ involved in anticompetitive agreements methods to either waive the entire fine or to diminish it considerably. The aim is to encourage companies to bring upfront anticompetitive agreements that aim to distort competition and free market, thus protecting the internal market. The competition law itself does not pursue to sanction players that acted in an anticompetitive manner, but to prevent such behavior, because prevention is more important than reducing the effects afterwards. In the present paper we aim to make a radiography of the methods of eliminating or reducing a fine that a company have in our national law when it comes to anticompetitive agreements.